Plasmonic Organic Solar Cells Charge Generation and Recombination - Wu, Bo.; Mathews, Nripan; Sum, Tze-Chien.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book explores the incorporation of plasmonic nanostructures into organic solar cells, which offers an attractive light trapping and absorption approach to enhance power conversion efficiencies. The authors review the latest advances in the field and discuss the characterization of these hybrid devices using a combination of optical and electrical probes. Transient optical spectroscopies such as transient absorption and transient photoluminescence spectroscopy offer powerful tools for observing charge carrier dynamics in plasmonic organic solar cells. In conjunction with device electrical characterizations, they provide unambiguous proof of the effect of the plasmonic nanostructures on the solar cells' performance. However, there have been a number of controversies over the effects of such integration - where both enhanced and decreased performance have been reported. Importantly, the new insights into the photophysics and charge dynamics of plasmonic organic solar cells that these spectroscopy methods yield could be used to resolve these controversies and provide clear guidelines for device design and fabrication.
Introduction -- Surface Plasmon Resonance -- Characterization Techniques -- Plasmonic Entities within the Charge Transporting Layer -- Plasmonic Entities within the Active Layer -- Concluding Remarks.
Keywords: Renewable energy sources; Optical materials; Lasers; Microtechnology; Microelectromechanical systems; Electric power production; Renewable Energy; Optical Materials; Laser; Microsystems and MEMS; Electrical Power Engineering; Mechanical Power Engineering